Implementasi Model Pembelajaran CORE (Connecting, Organizing, Reflecting, Extending) Ditinjau Dari Karakter Matematika - Nasrulloh, M Farid; Maulana, Shifa; Satiti, Wisnu Siwi; Khotimah, Khusnul (JoEMS (Journal of Education and Management Studies), 2022)
The purpose of this research is to measure the mathematical attitude of class VIII MTsN 3 Jombang students when the CORE (Connecting, Organizing, Reflecting, Extending) learning model is applied. The method used in this study is an experimental method in the form of a pre-experimental design with the type of one-shot case study. The subjects of this study were students of class VIII D at MTsN 3 Jombang. The instruments used for data collection were observations and questionnaires to measure the value of students' attitudes when applying the CORE learning model. The analysis technique used is descriptive analysis. Based on calculations from the results of observations and questionnaires, the attitude value of the questionnaire was 1335 from a perfect score of 1716 while from observation was 956 from a perfect score of 1248. The percentage of the data was 77.8% of the questionnaire data and 76.6% of the observation data and the average the average of these percentages is 77.3%. Because the student's attitude value is > 70%, it is declared successful. That is, the predicate of the attitude value of class VIII D students at MTsN 3 Jombang when applying the CORE learning model is in the good category.